The Application of Fluorescence Optical Imaging in Systemic Sclerosis. (18th August 2015) - Pfeil, Alexander; Drummer, Karl F.; Böttcher, Joachim; Jung, Christian; Oelzner, Peter; Renz, Diane M.; Franz, Marcus; Hansch, Andreas; Wolf, Gunter
Abstract : Objective . The aim of this study was to visualize soft tissue inflammation using FOI on patients with Systemic Sclerosis (SSc) characterized by SSc-related Raynaud's phenomenon and to detect the therapeutic response to treatment with iloprost or alprostadil. Methods . Twenty-one patients with SSc and Raynaud's phenomenon and twenty-six healthy controls were prospectively included. The SSc patients were intravenously treated with iloprost or alprostadil over seven days. FOI was performed at baseline and after seven days using an intravenous application of indocyanine green (ICG). The hands were divided into nineteen segments per hand. All segments were quantitatively evaluated to determine changes in ICG. Results . The sensitivity and specificity of FOI in the detection of ICG enhancement in patients with SSc were 95% versus 96%. At baseline, 31.5% hand segments showed ICG enhancement. After seven days of either iloprost or alprostadil therapy a significant reduction in the ICG was observed which ranged from 40.9% to 24.7%. Conclusion . The study demonstrates that the FOI technique is able to visualize soft-tissue inflammation with both high sensitivity and specificity. The anti-inflammatory therapeutic effects of iloprost were slightly stronger than alprostadil. FOI offers promising benefits in the diagnosis and therapy of patients with SSc-associated Raynaud's phenomenon.